Radio frequency abnormal dielectric response of manganese chromite (MnCr2O4) nanoparticles synthesized by coprecipitation method. (April 2016) - Gul, Muhammad
Graphical abstract: Highlights: Uniform MnCr2 O4 nanoparticles synthesized by surfactant-free coprecipitation route. XRD analysis confirmed the single spinel phase formation in the material. Dielectric loss was found abnormal over certain lower frequencies. AC conductivity proved the involvement of small polarons in conduction process. Abstract: Radio frequency dielectric behavior of nanocrystalline MnCr2 O4 synthesized via surfactant-free controlled coprecipitation route has been studied. Keeping in view the necessity of particle size uniformity and phase purity for genuine performance, experimental conditions were optimized accordingly. The scanning electron micrographs of the synthesized product revealed the formation of monodispersed particle system. X-ray diffraction analysis confirmed monophasic spinel structure formation with 65 nm crystallite size. Two characteristic peaks observed between 700 cm −1 and 400 cm −1 in the FTIR spectrum also supported the spinel phase purity of compound. The dielectric constant was found normal, but loss tangent of the sample showed abnormal behavior with frequency. The observed dielectric behavior of the synthesized product has been explained on the basis of space-charge polarization according to Maxwell–Wagner's model and mutual contribution of n -type & p -type charge carriers (Rezlescu model). The ac conductivity linearly increased with frequency highlighting the existence of polaron hopping.